Wyobraźnia turystyczna a obraz miasta w Zbrodni i karze Fiodora Dostojewskiego na lekcji języka polskiego w szkole ponadpodstawowej - Wawer, Karolina (Wydawnictwo Uniwersytetu Rzeszowskiego, 2023)
Celem artykułu jest zestawienie nowoczesnego imaginarium podróżniczego z obrazem Petersburga z kart Zbrodni i kary. Wiedza o sposobach podróżowania i wyobrażania sobie atrakcji turystycznych, uwzględnienie współczesnych teorii dotyczących podróży w celu interpretacji świata powieści, pozwoli na żywy i pogłębiony kontakt z lekturą, zgodnie z zasadami nowoczesnej dydaktyki. W artykule zebrano propozycje dydaktyczne dotyczące omówienia powieści Fiodora Dostojewskiego, wnioski płynące z przeprowadzonej lekcji oraz fragmenty prac uczniowskich.

The aim of the article is to juxtapose contemporary travel imaginings with the depiction of Petersburg on the pages of “Crime and Punishment.” Knowledge about modes of travel and envisioning tourist attractions, taking into account modern theories of travel to interpret the novel’s world, will allow for a lively and profound engagement with the reading, in accordance with the principles of modern teaching methods. The article gathers didactic proposals related to discussing Fyodor Dostoevsky’s novel, insights derived from the conducted lesson, and excerpts from student works.
Tourist Imagination and the Image of the City in Fyodor Dostoevsky’s “Crime and Punishment” in a Polish Language Class in Secondary School
Keywords: wyobraźnia turystyczna; obraz miasta; analiza literacka; metody nauczania w szkole ponadpodstawowej; tourist imagination; image of the city; literary analysis; teaching methods; secondary school